Corporate governance of Islamic financial institutions in Malaysia - Sulaiman, Maliah; Abd Majid, Norakma; Mohd Ariffin, Noraini (University of Malaya, 2015)
Given the phenomenal increase in Islamic banking activities globally, it is important that there exists good governance practices of Islamic financial institutions (IFIs). This is primarily to ensure its sustainability in the long run. More importantly, in order for Islamic banks to play an optimum role in the development of Islamic countries, it is imperative to develop regulatory structures which can help to control fraud, exploitation, and un-Islamic behaviour in banking practices. Additionally, the development of strong governance practices will win public confidence, thereby promoting trust amongst equity holders, investors and other parties dealing with these IFIs. However, promulgating and developing standards and guidelines on corporate governance (CG) may not be adequate. Thus, this paper examines the extent IFIs are adhering to such guidelines. There are two stages to this study. First a disclosure index was developed using the guidelines issued by the Central Bank of Malaysia (BNM), the standard on CG promulgated by the Accounting and Auditing Organization of Islamic Financial Institutions (AAOIFI) and the framework introduced by the Islamic Financial Services Board (IFSB). The index developed in the first stage was then used to assess the annual reports of all the 16 IFIs operating in Malaysia. It was found that on a scale of 0 to 100, the CG disclosure index ranges from a low of 42.28 to a high of 68.29, with the average score of 51.42. This shows that IFIs are not particularly motivated to disclose specific-governance related information. On the basis of the stewardship theory, however, these elements reflect the accountability of IFIs towards their stakeholders. Keywords: Corporate Governance Disclosure Quality, Islamic Financial Institutions (IFIs), Malaysia